ANALISIS UPAYA RUMAH SAKIT ISLAM SULTAN AGUNG KOTA SEMARANG SEBAGAI FASILITAS KESEHATAN TINGKAT LANJUT DALAM PENERAPAN PROGRAM JAMINAN KESEHATAN NASIONAL TAHUN 2014 - Puri Nur Mahmudah; Chriswardani Suryawati; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2015)
Communities are entitled to the protection of health and the state arranged for the fulfillment of a healthy life. The state develops social assurance system for all people. Implementing the national social assurance system which is done by health insurance BPJS health. The implementation of the health insurance program needs support from health facilities including private hospitals. One of the private hospital that are implementing the of health care benefit is RSI Sultan Agung. Based on preliminary survey known that there are still problems about the process of filing a claim. The percentage of patients participant BPJS health and the patient's health continues to increase GENERAL tends to decrease. The purpose of this study was to describe the efforts of Sultan Agung Islamic Hospital in implementing health assurance program of variable inputs and process. The form of descriptive research with a qualitative approach. The subject of research is board of directors, the head of state and staff. The informant triangulation of patients and unit head referral services management the BPJS Health. The results of research that the input variables consist of human resources, funds, infrastructure, procedures and policies, and information. While the process variables consist of team building JKN, INA CBG's claims management and health care. Human resources experienced an increase in staff and training staff there are ever followed: Funding comes sourced from claims ina cbg not managed in a special hospital and entering the public revenue and used for operational hospital : Conducted the relocation of the infrastructure, the addition of VIP room, VVIP & room team JKN, system and succeeded in bridging: procedures be performed rekredensialing BPJS partners, coordination of benefits procedure has not been carried out in cooperation with the private commercial insurance, existing policies on the cost and quality control, costs iur policy: information such as the flow of information to staff to patients, coordination and flow of complaints. The formation of the team JKN selected based units that are involved in the health insurance program: INA CBG's claims management already made a request refisi rates: health care guided by the clinical pathways of the Hospital.